Russia's hybrid threats as the biggestobstacle to the euro integration process in the Western Balkans a case study of Bosnia and Herzegovina and Serbia - Martin Solik; Jan Graf (University American College Skopje, 2022)
This study addresses Russian hybrid threats in the Western Balkans in the context of the ongoing European integration process. Two countries were selected for this purpose: Bosnia and Herzegovina and Serbia. This study is based on field research conducted in Sarajevo, Novi Sad and Belgrade in August 2021. The authors of this study conducted a total of 9 expert interviews, based on which they were able to determine how the creation of Russian hybrid threats negatively affects the accession negotiations taking place between the representatives of the European Union and the top officials of the two mentioned countries. Based on an interpretive case study, the authors were able to identify Russian hybrid threats in three areas. Russian political influence, the Kremlin's energy policy, and last but not least Moscow's disinformation campaigns aimed at discrediting Euro-Atlantic integration structures in general are involved in slowing down the accession negotiations between the EU and the Western Balkan states.
Keywords: 330; Western Balkans; Russia; Bosnia and Herzegovina; Serbia; EU; Dodik; Putin